2006
DOI: 10.1002/jbm.b.30522
|View full text |Cite
|
Sign up to set email alerts
|

Medium (DMEM/F12)‐containing chitosan hydrogel as adhesive and dressing in autologous skin grafts and accelerator in the healing process

Abstract: Autologous skin grafts are considered necessary for the treatment of extensive skin defects. However, skin graft by suturing is a time-consuming medical handling and rather stressful event for recipients. To that end, tissue adhesives have been suggested in skin grafts. Chitosan hydrogel is well known as a wound dressing and tissue adhesive material showing biocompatibility, anti-infective activity, and the ability to accelerate wound healing. In this report, we evaluated the application of the chitosan hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…This data further confirmed that in addition to hydrolysis, efficient inflammatory cell penetration during the healing process of burn wounds accelerated the degradation of the hydrogel more than control scaffold. Our data agrees with the results of another study suggesting that neutrophils promoted chitosan hydrogel degradation (23). Additionally, recent studies demonstrated that a degradable hydrogel allowed and directed cell growth in vitro (31, 32) compared to nondegradable hydrogels.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This data further confirmed that in addition to hydrolysis, efficient inflammatory cell penetration during the healing process of burn wounds accelerated the degradation of the hydrogel more than control scaffold. Our data agrees with the results of another study suggesting that neutrophils promoted chitosan hydrogel degradation (23). Additionally, recent studies demonstrated that a degradable hydrogel allowed and directed cell growth in vitro (31, 32) compared to nondegradable hydrogels.…”
Section: Resultssupporting
confidence: 83%
“…Many studies of hydrogel-based scaffolds have focused on applications in healing wounds (5,(16)(17)(18)(19)(20)(21). Beyond their utility as scaffolds, hydrogels can also deliver cytokines and growth factors (22,23), antibiotics (20), and cells (24,25) to allow complete skin regeneration.…”
mentioning
confidence: 99%
“…19,20) Hydrogels provide a cover on the wound in the absence of injured skin integrity. An ideal gel formulation used for burn healing should be easily applicable and retained for a long time on the wound.…”
Section: Resultsmentioning
confidence: 99%
“…Both biopolymers have b-glucosidic bonds and very similar structure. Their somewhat unique properties; especially the strong mechanical strength, biocompatibility and thermal stability of cellulose (Nishio 1994;Yamashiki et al 1990), and the wound healing, antibacterial properties of chitosan (Burkatovskaya et al 2006;Jain and Banerjee 2008;Kiyozumi et al 2006;Shepherd et al 1997), as well as their ability of self-assembly into intriguing micro-or nano-sized structures (Qiu and Hu 2013;Wu et al 2016;Zhang et al 2016), provide many options and ideas for functional materials design.…”
Section: Introductionmentioning
confidence: 99%